Teaching Foreign Languages Using Storytelling as An Academic Process (مجلة إحالات, 2026)
Nowadays, teachers use many tools and methods to improve learning and teach foreign languages mainly the English language. For that, they use different techniques such as storytelling,proverbs, poems, idioms, jokes, etc. For the aim of providing learners to build their cultural knowledge and gain fruitful results of the target language. In fact, in middle and secondary school storytelling canbe taken as a funny source of information for learners since giving much importance to teaching grammar and phonetics rules makes the learning process difficult and boring. Besides, students at this level need to discover more about the culture of the foreign language. To this aim, the rationale of the current research paper is to explore teachers’ and learners’ attitudes towards teaching the English Language through using storytelling. Moreover, another concern of the current research paper is to promote in-depth research on whether the use of storytelling is beneficial indeveloping the learners’ cultural awareness of the target language, creating an enjoyable atmosphere, and improving the four linguistic skills or not. To achieve this claim, this research paper gives an in-depth look at teaching by using a storytelling-based approach through reaching asystematic analysis based on a questionnaire, an interview, and classroom observation. To this end, the findings revealed that both teachers and learners believe that the introduction of storytelling in learning a foreign language may improve their vocabulary and understanding. The results also demonstrated that learners enjoy the learning process by using a storytelling-based approach during their practical sessions.